Job satisfaction as a mediator in improving employee performance through talent and knowledge management - Indra Setia, Bayu; Yuniarsih, Tjutju; Gaffar, Mohammad Fakry; Suryadi, Edi; Affandi, Azhar; Rohmawati, Tatik (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This study aims to analyze Job Satisfaction as a Mediator in Improving Employee Performance through Talent and Knowledge Management. The data analysis used is verification analysis. The population is focused on 16 logistics service companies in the city of Bandung. The analytical tool used is the Structural Equation Model (SEM)-PLS, data obtained through questionnaires to 160 employees. The findings reveal that talent management and knowledge management make a positive contribution to job satisfaction, either partially or simultaneously, which has an impact on employee performance. This is because logistics services will always innovate in accordance with good knowledge management and talent management, therefore employees are required to express their thoughts, ideas and abilities to achieve all of this. This research adds to knowledge about how logistics service companies can manage talented employees and knowledge management that can lead to increased job satisfaction which has an impact on employee performance.